(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Ranitidine is a generic antacid most commonly sold as Zantac. Ranitidine was popular in the United States even without a prescription until April 2020. The Food and Drug Administration (FDA) came to the conclusion that NDMA levels in ranitidine increased under ordinary storage settings, and that these thresholds increased significantly at higher temperatures. NDMA has been found to be a possible human carcinogen by independent testing, after being reported to become an efficacious carcinogen in experimental animals. Methods: A number of databases, such as PubMed, Cochrane Central Register and EMBASE, were searched to locate all qualified trials for Ranitidine contained NDMA, a carcinogen. In a PubMed search, 664 papers were identified till October 31, 2022, identical articles were removed, and lastly, 8 papers were included for the systemic review and meta-analysis. Results: Figures and tables were used to sum up Meta-regression results and the NDMA ddose-responseanalysis results. Relative Risk (R.R.) was used to assess the relationship between dietary intake of NDMA nitrates and nitrites and cancer risk. In this study, we take a look at the findings from other studies that have been done previously that showed NDMA (nitrosamines) use increased the risk of cancer by a lot. Several studies have also looked at the link between working with or eating NDMA and taking Ranitidine, which has been linked to cancers of the liver, GI tract, esophagus, pancreas, and colon. Conclusions: This study provided a summary of an article on dietary NDMA, including Ranitidine contamination exposure related with a significant statistical increased incidence of gastrointestinal cancers.